Study on marathwada davisgender and identity - MD. EHSHAM (International Journal of Multidisciplinary Research and Studies, 2021)
Feminism has historically been and will continue to be seen as a movement in its own right, on par with any other movement, whether it socially or physically. Sometimes it obtains a place in literature among all the other theories that take a less emotional approach to the subject matter. The concept of feminism has been passed down to us or has developed through time as a theory, but the majority of women, who make up a marginalized part of society, have changed very little over the course of the years. We are still engaged in the age-old conflict of repression and suppression; we are still subjected to the same mental and physical humiliation; we are still required to endure the same pain just because we were born female. The struggles and the shame that come along with being humiliated as a woman are timeless. There does not seem to be any way out of the mental and physical abuse that women are subjected to in today's culture. In her writings, Mahasweta Devi elucidates the challenges that women face and the suffering that they go through as a result of living in a society that is controlled by males. In her writings, she has addressed the predicament of women and their inferior status in society. Her writing has little to do with the small daily quirks of the affluent, and she avoids the unneeded or unnecessary. Her avoidance of the needless or unnecessary is reflected in her writing. Her writing is factual and without of hyperbole, thus there is no room for sentimentality in her portrayal of the predicament of women who are most severely and directly impacted by patriarchy. Her protagonists come from lower-class socioeconomic backgrounds, and they are believable, multifaceted, and completely fleshed-out individuals.